Phytochemical analysis and correlation of total polyphenol content and antioxidant properties of Symplocos cochinchinensis leaves - Hai Trieu Ly; Vu Khanh Trang Le; Van Minh Le; Cong Sanh Phan; Chau Tuan Vo; Minh Ly Nguyen; Thi Anh Dao Phan (Vietnam Journal of Science, Technology and Engineering, 2022)
This study screened phytochemicals to determine their total polyphenols content (TPC) by Folin-Ciocalteu reagents and to evaluate antioxidant activity using DPPH scavenging, ABTS cation decolorization, and reducing power assays of various extracts of Symplocos cochinchinensis leaves. A correlation between TPC and antioxidant activity was analysed by Pearson’s method. The results indicated that S. cochinchinensis leaves contained triterpenoids, alkaloids, anthraglycosides, flavonoids, anthocyanosides, proanthocyanidins, polyphenols, tannins, saponins, polyuronics, and reducing agents. All extracts had antioxidant properties with the ethyl acetate fraction exhibiting the highest antioxidant capacity, which had the lowest IC50 in DPPH (83.33 μg/ml), an ABTS of 46.21 μg/ml, and EC50 of 69.10 μg/ml in reducing power. There was a significant negative correlation between the TPC in S. cochinchinensis leaf extracts and their IC50 and EC50 values of antioxidant activity. It was suggested that S. cochinchinensis leaves have a great potential for antioxidant activity based on its high total polyphenol content and potential for use as a traditional treatment.